Public bus transport service satisfaction: Understanding its value to urban passengers towards improved uptake - Hasan, U.; Whyte, Andrew; Jassmi, H.A. (2021)
To accurately direct investments towards sustainable transit, current transport status and factors driving passengers towards private cars instead of public transport (PT) should be identified first. Past research advocated improvements in PT to shift mode-usage but has yet to model the different causal effects that direct bus users to cars in rapidly developing yet congested areas. On-board questionnaire survey data from intra-city Abu Dhabi bus passengers (n = 1520, variables = 31) over a month were gathered in this study during both weekends and weekdays. The study modelled existing bias of travellers and quality attributes as antecedents of bus service's perceived value for money (VfM) and satisfaction from level of service (LoS) and mode choice (car vs. bus) as the ultimate consequence. Findings revealed that any previous biased opinions of travellers adversely affected satisfaction and perceived value, while quality attributes had a positive effect. Mode use was influenced by satisfaction from LoS (frequency of buses and network coverage), which was a positive consequence of perceived VfM (quality of ride and level of fare trade-off). Journey time and bus-stop waiting area quality also positively influenced satisfaction from fare level while passenger sociodemographic distribution showed that most respondents travelled more than five times a week by bus and were full-time workers and transport agencies may target service improvements around office-hours.